Self-assembled FGF21 nanoparticles alleviate drug-induced acute liver injury - Huang, Zhiwei; Wang, Hengcai; Chun, Changju; Li, Xinze; Xu, Shihao; Zhao, Yingzheng (Frontiers in Pharmacology, 2023)
Acetaminophen (N-acetyl-p-aminophenol, APAP) is a common antipyretic agent and analgesic. An overdose of APAP can result in acute liver injury (ALI). Oxidative stress and inflammation are central to liver injury. N-acetylcysteine (NAC), a precursor of glutathione, is used commonly in clinical settings. However, the window of NAC treatment is limited, and more efficacious alternatives must be found. Endogenous cytokines such as fibroblast growth factor (FGF) 21 can improve mitochondrial function while decreasing intracellular oxidative stress and inflammatory responses, thereby exhibiting antioxidant-like effects. In this study, self-assembled nanoparticles comprising chitosan and heparin (CH) were developed to deliver FGF21 (CH-FGF21) to achieve the sustained release of FGF21 and optimize the in vivo distribution of FGF21. CH-FGF21 attenuated the oxidative damage and intracellular inflammation caused by APAP to hepatocytes effectively. In a murine model of APAP-induced hepatotoxicity, CH-FGF21 could alleviate ALI progression and promote the recovery of liver function. These findings demonstrated that a simple assembly of CH nanoparticles carrying FGF21 could be applied for the treatment of liver diseases.